Enhancing Student Activity through Learning Gamification: A Quantitative Analysis - Lily Alamanda; Najih Anwar (Indonesian Journal of Islamic Studies, 2024)
This study investigates the impact of learning gamification on student activity and explores the strength of their correlation. Employing a Pre-Experimental One-Shoot Case Study design, both quantitative and qualitative data were collected and analyzed using the SPSS application (version 19.0). The Pearson product moment correlation test and simple linear regression test were applied to validate the data. The research encompassed 126 students from MI Muhammadiyah 2 Kedungbanteng, with a sample size of 17 students. The findings revealed a significant influence of learning gamification on student activity, supported by a strong correlation of 0.924. This study underscores the potential of gamification in enhancing student engagement and offers valuable insights for educators seeking to optimize learning experiences. Highlight: This study explores the impact of learning gamification on student activity and assesses the strength of their relationship. Both quantitative and qualitative data were collected and analyzed using SPSS, employing correlation and regression tests for validation. The findings highlight a significant positive influence of learning gamification on student engagement, with a strong correlation coefficient of 0.924. This emphasizes the potential of gamified approaches in optimizing educational experiences. Keyword: Learning Gamification, Student Activity, Correlation, Educational Enhancement, Optimization Insights